Analysis of Coral Reef Cover in Nias Regency, North Sumatra - Simaremare, Elisabet Rosevenny; Wahyuningsih, Hesti; Aththorick, T Alief (Tunas Geografi, 2024)
Marine and fisheries resources in the waters of Nias Regency are one of the sectors that drive the community's economy, especially in coastal areas. Coral reefs are one of the marine ecosystems in Nias Regency that have high ecological and economic value. This research aims to evaluate the environmental conditions of coral reefs in the Nias Regency Water Area, especially in the seascape tourism zone around the waters of Onolimbu Island and Musi Island as research locations. The research was conducted from March to May 2023 in the coastal waters of Nias Regency to collect ecological and socio-economic data. Coral cover analysis was carried out using underwater photo methods and classified based on condition categories set by the Ministry of Environment. The condition of coral reefs at this research location is in the damaged to moderate category (23.47-45.13%) with an average abundance of 31.54% and is included in the medium category. The percentage of coral reef life form types consists of Dead Coral Algae (DCA) (34.86%), Hard Coral (31.81%), Sands (15.73%), Recent Dead Coral (5.84%), and the rest are Rubble, Other Biota and Rock. Coral Reefs, Coral Cover, Nias Regency